Rancang Bangun Sistem Informasi Berbasis CustomerRelationship Management (CRM) Pada Heri Cafe - Yulia Putri Afivah; Syefrida Yulina (ABEC Indonesia, 2022)
Heri cafe is one of the cafes located on Jalan Lintas Ujung Tanjung, Tanah Putih sub-district, RokanHilir Regency. The improvement of the economy in the Rokan Hilir area is followed by an increase in people'sincome, especially the Ujung Tanjung area which can change people's lifestyles to become consumptive.Characteristics of people who tend to have a lifestyle that likes to hang out which encourage more and morehangout places such as cafes to be opened. Heri cafe still uses the manual method, namely by direct buyers comingto order the cafe menu, transaction data is also still written using notes and customer data has never beenrecorded so that they cannot determine the right strategy to continue to provide maximum service to cafe visitors.Heri cafe also still uses social media Facebook and Instagram to get complete information about the discountsprovided. With these problems, a system was built by applying the Framework of Dynamic CRM as one of thefeatures contained in CRM, aiming to obtain customer satisfaction information from customers so that the outputis Relationship Commitment (a committed relationship), namely loyal customers to Heri cafe, This system usesthe PHP (Hypertext Preprocessor) programming language, and MySQL as the database. Blackbox testing foundthat 100% of the system functionality went well and usability testing was applied to 30 respondents, namelyefficiency aspect 82.4%, learning aspect 86.75%, memory aspect 88%, aspect error 93%, satisfaction aspect 96.5%. From these 5 usability characteristics, an average of 89.33% of respondents stated that this system has beenaccepted by users.